2013
DOI: 10.1186/1752-153x-7-86
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective hydrolyzation and photolyzation of dufulin in water

Abstract: BackgroundDufulin is a novel, highly effective antiviral agent that activatives systemic acquired resistance of plants. This compound is widely used in China to prevent and control viral diseases in tobacco, vegetable and rice. Dufulin can treat plants infected by the tobacco mosaic virus and the cucumber mosaic virus. However, the achiral analysis and residue determination of dufulin remain underdeveloped because of its high enantioselectivity rates and high control costs. The enantioselectivity of an antivir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…Much work has not been carried out on enantioselective degradation of dufulin pesticide. However, the efforts were made to compare the results with those available in the literature . The values of the rate constant reported were in the range of 0.0083 to 0.0339 d −1 while the values of the rate constant described in this manuscript were in the range of 0.05 to 0.051 d −1 .…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Much work has not been carried out on enantioselective degradation of dufulin pesticide. However, the efforts were made to compare the results with those available in the literature . The values of the rate constant reported were in the range of 0.0083 to 0.0339 d −1 while the values of the rate constant described in this manuscript were in the range of 0.05 to 0.051 d −1 .…”
Section: Resultsmentioning
confidence: 79%
“…It is used to control plant viruses like tobacco and cucumber mosaic virus, potato virus Y, tomato mosaic virus, and the southern rice black streaked dwarf virus. There are not many studies on the toxicity profile of dufulin . However, Rulcova et al reported some toxicity when dufulin was injected into rats.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that significant enantioselectivity of acephate and methamidophos probably occurred during tea infusion. However, the reason for this 49 which needs further investigation. Transfer rates of acephate and methamidophos enantiomers were higher than 80.5% and 89.1%, respectively.…”
Section: Enantioselective Dissipation Of Residues In Fresh Teamentioning
confidence: 93%
“…At present, studies of dufulin are mainly focused on antiviral activity (Chen et al, ; Hu et al, ; Wang et al, ), residual analysis (Chen et al, ; Chen, Li, et al, ; Li et al, ; Lu, Yang, Hu, Ding, & Shi, ; Miao, Wang, Lu, Geng, & Yang, ; Zhang, Meng, et al, ; Zhu et al, ) or degradation mechanisms in an achiral way (Wang et al, ). Moreover, only three papers have reported on the enantioselective separation of dufulin (Zhang et al, ; Zhang, Hu, Zhu, Yang, & Song, ; Zheng et al, ). For example, Zhang, Hu, et al () established a simple chiral separation of dufulin by normal‐phase high‐performance liquid chromatography in soil, and Zheng et al () used ultra‐high‐performance liquid chromatography with high‐resolution mass spectrometry to determine two dufulin enantiomers in watermelon.…”
Section: Introductionmentioning
confidence: 99%